COMPARISON OF EFFECTIVENESS OF METFORMIN WITH NUTRITIONAL COUNSELLING ON GLYCEMIC CONTROL IN PRE-DIABETICS (The Research of Medical Science Review, 2025)
Background: Prediabetes, a condition where blood glucose levels are higher than normal but not yet in the diabetic range, affects many individuals worldwide. This condition arises when the body fails to produce enough insulin, causing glucose to stay in the blood. Objective: The main objective of the study is to find the comparison of effectiveness of metformin with nutritional counselling on glycemic control in pre-diabetics. Methodology: A six-month cohort study was conducted at Pak Emirate Military Hospital (PEMH) in Pakistan from June to November 2023 to compare the effectiveness of Metformin and nutritional counseling in controlling glycemic levels. The study included 120 participants with prediabetes, divided into two groups: 60 received Metformin and 60 received nutritional counseling. Results: It evident from study that Metformin significantly improved glycemic control, with a 15% reduction in fasting blood glucose levels and an average decrease of 1.9% in HbA1c levels. The nutritional counseling group also demonstrated substantial benefits, with a 12% reduction in fasting blood glucose levels and an average decrease of 1% in HbA1c levels. Conclusion: Both Metformin and nutritional counseling effectively reduced blood glucose levels in individuals with prediabetes. Metformin was more effective, but nutritional counseling also had a significant impact.